High school teacher perceptions of implementation of evidence-based practices for classroom management. Issue 5 (20th October 2021) - Hepburn, Lorna; Beamish, Wendi; Alston-Knox, Clair L.
ABSTRACT: Evidence-based practices for classroom management are well established and predominantly preventative in nature. However, use of reactive practices by teachers has been widely reported internationally, particularly in middle and high school settings. Teachers ( N = 587) throughout government high schools in Queensland, Australia responded to a survey about their experiences and confidence with classroom management and their use of 14 evidence-based classroom management practices. Participating teachers reported being confident classroom managers and frequently using the majority of the presented practices. Practices related to teaching and reinforcing expected behaviours were reported to be more intermittently used. Contextual factors which help account for these findings are discussed.